Exploring the factors influencing the health-related quality of life in patients experiencing adverse drug reactions: a cross-sectional study - Garapati Pavan; Manish Kumar; Krishna Murti; Sameer Dhingra; V. Ravichandiran (SpringerOpen, 2024)
Abstract Background This study aimed to assess the factors influencing health-related quality of life (HRQoL) in patients experiencing adverse drug reactions (ADRs) at a tertiary care public sector hospital. A cross-sectional study was conducted over a period of 18 months, and included both male and female patients aged 18 years and above. Patients who visited the outpatient and inpatient departments with complaints associated with ADRs were included in this study. HRQoL data were collected using the EuroQol-5 Dimension-5 Level (EQ-5D-5L) questionnaire to assess five dimensions of health on a five-level scale. Descriptive statistics, t-tests, and analysis of variance were used to analyze the data. Multivariate regression analysis was performed to identify the potential determinants of HRQoL. Results A total of 316 patients were included in the study among these participants, of which 54% were female, and 65% were from rural areas. The majority (68%) of the patients had moderately severe ADRs, and 63% of the participants had an income < 2.5 lakh Indian rupees (3009 USD). The mean EQ-5D-5L and EuroQoL Visual Analog Scale (EQ VAS) scores of the study participants were 0.714 and 69.73, respectively. The variables ADR severity, income, and age showed a significant difference (p < 0.05) in HRQoL. Conclusion This study provides insights into HRQoL among patients with ADRs and identifies the determinants of HRQoL. The findings of this study will contribute to improving patient-centered care and optimizing patient outcomes.